Molecular characterization of cell-free eccDNAs in human plasma - Zhu, Jing; Zhang, Fan; Du, Meijun; Zhang, Peng; Fu, Songbin; Wang, Liang (Scientific reports, 2017)
Extrachromosomal circular DNAs (eccDNAs) have been reported in most eukaryotes. However, little is known about the cell-free eccDNA profiles in circulating system such as blood. To characterize plasma cell-free eccDNAs, we performed sequencing analysis in 26 libraries from three blood donors and negative controls. We identified thousands of unique plasma eccDNAs in the three subjects. We observed proportional eccDNA increase with initial DNA input. The detected eccDNAs were also associated with circular DNA enrichment efficiency. Increasing the sequencing depth in an additional sample identified many more eccDNAs with highly heterogenous molecular structure. Size distribution of eccDNAs varied significantly from 31 bp to 19,989 bp. We found significantly higher GC content in smaller eccDNAs (<500 bp) than the larger ones (>500 bp) (p < 0.01). We also found an enrichment of eccDNAs at exons and 3′UTR (enrichment folds from 1.36 to 3.1) as well as the DNase hypersensitive sites (1.58–2.42 fold), H3K4Me1 (1.23–1.42 fold) and H3K27Ac (1.33–1.62 fold) marks. Junction sequence analysis suggested fundamental role of nonhomologous end joining mechanism during eccDNA formation. Further characterization of the extracellular eccDNAs in peripheral blood will facilitate understanding of their molecular mechanisms and potential clinical utilities.